2006
DOI: 10.1128/aac.50.5.1615-1622.2006
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines Induce Resistance to Cationic Peptide, Aminoglycoside, and Quinolone Antibiotics in Pseudomonas aeruginosa PAO1

Abstract: Pseudomonas aeruginosa, a gram-negative bacterium of human pathogens, is noted for its environmental versatility, enormous metabolic capacity, and resistance to antibiotics. Overexpression of the outer membrane protein OprH and increased resistance to polycationic peptide antibiotics (e.g., polymyxin B) mediated by the PhoPQ two-component system on induction of a putative lipopolysaccharide (LPS) modification operon (PA3552-PA3559) have been reported as part of the adaptive responses to magnesium limitation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 23 publications
3
99
0
Order By: Relevance
“…Exogenous spermidine added to culture medium increases the resistance of Pseudomonas aeruginosa to aminoglycosides and quinolones, although no known efflux system was found to be significantly upregulated using DNA microarray analysis (Kwon & Lu, 2006). In this study, we tracked the changes in intracellular levels of spermidine and N-acetylspermidine during growth of B. pseudomallei KHW and describe the effect of such changes on the expression of the BpeAB-OprB pump, which is involved in the efflux of mostly N-acetylspermidine.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous spermidine added to culture medium increases the resistance of Pseudomonas aeruginosa to aminoglycosides and quinolones, although no known efflux system was found to be significantly upregulated using DNA microarray analysis (Kwon & Lu, 2006). In this study, we tracked the changes in intracellular levels of spermidine and N-acetylspermidine during growth of B. pseudomallei KHW and describe the effect of such changes on the expression of the BpeAB-OprB pump, which is involved in the efflux of mostly N-acetylspermidine.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, polyamines can modify the response of microbes to antibiotics, depending on their chemical characteristics, the bacterial target, or the antimicrobial agent under investigation (7,11,21); however, specific molecular mechanisms to explain how polyamines function in this capacity remain to be determined. Since previous studies with Escherichia coli and Pseudomonas aeruginosa showed that polyamines can bind to bacterial surfaces and influence the antimicrobial action of different antibiotics (13,34), we hypothesized that similar relationships may hold for N. gonorrhoeae and host-derived antimicrobials. We now report that incubation of gonococci with sublethal levels of polyamines (e.g., spermine) reduces their susceptibility to the killing action of two structurally diverse CAMPs (PMB and LL-37) and to complement-mediated killing by NHS.…”
mentioning
confidence: 99%
“…Although polyamines have not been shown to induce expression of efflux pumps, spermidine did provide resistance against cationic peptides and quinolones by inducing expression of oprH-phoPQ and the LPS modification operon (885). It is likely we don't yet know all the current targets of polyamines.…”
Section: Regulation Ofmentioning
confidence: 99%
“…Previous work showed that polyamines decreased expression of T3SS secretions and virulence genes in PA01 (884). Polyamines were also shown to increase resistance in P. aeruginosa against aminoglycosides, with resistance against quinolones and cationic peptides being mediated by the expression of the oprH-phoPQ operon (885). In contrast, polyamines significantly increased susceptibility of P. aeruginosa against a number of β-lactams including the penicillins ampicillin, carbenicillin, piperacillin and ticarcillin, and the third generations cephalosporins ceftazidime, cefoperazone and ceftriaxone (886).…”
Section: Generation Of the Transposon Librarymentioning
confidence: 99%